Spot Distribution and Evolution on Two New Active Binaries Discovered in the YNHK Survey - Jianhua Wang; Shenghong Gu; Xiaobin Wang; Bill Yeung; Eric Ng; Kamfung Yu; Leilei Sun; Yue Xiang; Dongtao Cao; Baoli Lun; Yuxin Xin; Fukun Xu; et al. (The Astronomical Journal)
The study on active binaries can provide detailed insights to understand how binarity affects dynamo actions inside stellar interiors. Here we report two active eclipsing binaries, USNO-B1.0 0743-0306638 and 0763-0282368, discovered in the Yunnan–Hong Kong wide-field photometric (YNHK) survey. Both of the two systems are detached binaries and show spot activities, while USNO-B1.0 0763-0282368 is more close to its Roche lobe. By means of the Wilson–Devinney (WD) code, their photometric solutions are determined based on parts of the YNHK photometric light curves. Furthermore, the spot distribution and evolution are investigated using time series of the YNHK light curves from 2016 to 2023. The results show that the spot activities appeared on the primary components for the two binary systems. There exist two kinds of spots: one is polar spots that lead to the variation of overall luminosity of the binaries, while the other is low-latitude spots that cause the rotational modulation. The polar spots behave more long-lived than the low-latitude spots on both binaries. For the low-latitude spot, its longitudinal distribution becomes more stable and closer to the substellar point as the binary system is close to the Roche lobe.